Overview of non-clinical safety assessment in drug development - Herzyk, Danuta (Henry Stewart Talks, 2010)
Toxicology studies of drug candidates as a critical part of safety evaluation in non-clinical and clinical development of new medicines, Goals, types and extent of toxicity studies in different phases of drug development, Comparison of small chemical drugs and large therapeutic molecules (biopharmaceuticals)
Archived at 2020/09/30